Wikis na produção textual colaborativa de notícias on-line em inglês como L2 no meio virtual: um estudo de caso - Valeria Augusta Rocha de Assis Santos (2011)
In this study, we observed the pedagogical potential of Wikis and their tools to support the process of collaborative learning. Our main aim was to understand how this technology can assist and favor the process of collaborative writing. Also, we aimed to investigate the influence of collaboration on the learning process and on the foreign language writing. This research was conducted in an undergraduate course at FALE UFMG. The study was grounded in theories of collaborative learning. In addition, it adopted a process and a genre orientation to writing instruction. The data collection instruments were questionnaires, the writings produced by the participants (individual and collaborative) and the observation of interactions in Wikispaces forum. The results showed that the wikis may: contribute to transform learners produsage capacities by creating opportunities to collaborate and produce knowledge; favor collective authoring and allow emphasis on the social dimensions of writing process. Moreover, it was possible to confirm the potential of the collaborative writing approach as we noticed that the contribution of each participant in the group work resulted in a better quality writing.